PLANT DISTANCE RESPONSE TO GROWTH AND RESULTS OF BUNCIS NUT (Phaseolus vulgaris L.) PLANTS IN VARIOUS SOLID BIOSLURRY DOSAGE - Sepvi Indah Purwanti (Universitas Islam Balitar, 2018)
This study aims at 1) to determine the interaction of planting spacing and bioslurry doses on the growth and yield of beans. 2) to determine the effect of planting distance on the growth and yield of beans. 3) to determine the effect of dense bioslurry doses on the growth and yield of beans. The research using Split Plot 2 factorial was repeated 3 times. The first factor is distance (J) which consists of 3 levels, namely: 20x50cm (J1), 20x60cm (J2), 20x70cm (J3). The second factor is a solid bioslurry dose (B) consisting of 3 levels: B1 = 500 kg. Ha-1, B2 = 600 kg. Ha-1, B3 = 700 kg. Ha-1. The results showed that there were interactions between plant spacing and bioslurry doses on the number of pods with the highest yield in J2B3 treatment, ie 59.33, pod weight by plant with the highest yield in J2B2 treatment, namely 390.27 gr / plant and pod weight by plot with the highest yield in J2B3 treatment, which is 5993.75 gr / plo